The Underlying Pathogenesis of Neurovascular Compression Syndromes: A Systematic Review - Szmyd, Bartosz; Sołek, Julia; Błaszczyk, Maciej; Jankowski, Jakub; Liberski, Paweł P.; Jaskólski, Dariusz J.; Wysiadecki, Grzegorz; Karuga, Filip F.; Gabryelska, Agata; Sochal, Marcin; Tubbs, R. Shane; Radek, Maciej (Frontiers in Molecular Neuroscience, 2022)
Neurovascular compression syndromes (NVC) are challenging disorders resulting from the compression of cranial nerves at the root entry/exit zone. Clinically, we can distinguish the following NVC conditions: trigeminal neuralgia, hemifacial spasm, and glossopharyngeal neuralgia. Also, rare cases of geniculate neuralgia and superior laryngeal neuralgia are reported. Other syndromes, e.g. disabling positional vertigo, arterial hypertension in the course of NVC at the CN IX-X REZ and torticollis, have insufficient clinical evidence for microvascular decompression. The exact pathomechanism leading to characteristic NVC-related symptoms remains unclear. Proposed etiologies have limited explanatory scope. Therefore, we have examined the underlying pathomechanisms stated in the medical literature. To achieve our goal, we systematically reviewed original English language papers available in Pubmed and Web of Science databases before ‎2 ‎October ‎2021. We obtained 1694 papers after eliminating duplicates. Only 357 original papers potentially pertaining to the pathogenesis of NVC were enrolled in full-text assessment for eligibility. Of these, 63 were included in the final analysis. The systematic review suggests that the anatomical and/or hemodynamical changes described are insufficient to account for NVC-related symptoms by themselves. They must coexist with additional changes such as factors associated with the affected nerve (e.g., demyelination, REZ modeling, vasculature pathology), nucleus hyperexcitability, white and/or gray matter changes in the brain, or disturbances in ion channels. Moreover, the effects of inflammatory background, altered proteome, and biochemical parameters on symptomatic NVC cannot be ignored. Further studies are needed to gain better insight into NVC pathophysiology.